The Use of Digital English Textbooks: A Study on Comprehension and Language Production Abilities Among Young Learners - Thea Karuni Respati; Bayu Hendro Wicaksono; Estu Widodo (Universitas Pendidikan Mandalika, 2024)
The shift from traditional to digital textbooks in education brings both prospects and hurdles, especially in teaching English to young learners. Despite the widespread adoption of digital textbooks, their impact on students' language skills and teacher-student interaction needs more exploration. This study aims to thoroughly evaluate how digital textbooks affect English comprehension and production among young learners and teachers. The research conducted at SDS Islam Ar-Risalah Jember involved two teachers and eleven students, employing a descriptive qualitative method. Observations, interviews, and document analysis were utilized to gather data, analyzed through the Miles and Huberman method, pinpointing trends in digital textbook usage and understanding. Results suggest digital English textbooks significantly improve young learners' and teachers' English skills, enhancing speaking, reading, writing, and listening abilities. These resources offer a dynamic and interactive educational experience. However, transitioning to digital tools introduces challenges like infrastructural limitations and the need for teaching method adjustments. Addressing these issues is essential for fully leveraging digital textbooks in education. In conclusion, while digital textbooks can boost English language mastery among young learners and teachers, realizing this potential requires overcoming certain technological and pedagogical obstacles.